Arus Terobosan Pada Transistor Dwikutub Struktur Hetero Si/Si1-xGex/Si Anisotropik Melewati Basis Tergradasi (Graded Base) - Hasanah, Lilik; Khairurrijal, Khairurrijal (BERKALA FISIKA, 2010)
Tunneling current in bipolar transistors Si/Si1-xGex/Si anisotropic hetero structure for germanium conditions on a constant basis is not analyzed here. The concentration of germanium in the base which is not constant will result in the potential profile at the base is not flat, but will be graded according to the germanium concentration. Tunneling current calculation is performed semi-analytically and numerically. The calculation result obtained then matched with experimental data. The results show that the results of analytical calculations with results of semi-numerical calculations. While analytical calculations with experimental data only flows from the VBE 0.3 to 0.6 V. Â Keywords: Tunneling current, germanium concentration, anisotropic material, transfer matrix method, hetero structure bipolar transistor